Comparison of the parasitic impedances from the drain‐source path of power transistor packages at up to 2 GHz. Issue 5 (16th December 2021) - Moldaschl, Thomas; Woetzel, Stefan; Latella, Riccardo; Galvano, Maurizio; Binder, Alfred
Abstract: In this article, we compare several concepts for gallium‐nitride (GaN) power high electron mobility transistor (HEMT) packages in terms of their drain‐to‐source parasitic inductance and resistance values. Unlike in previous studies, however, due to several fast transient use cases the investigated frequencies are extended to 2 GHz. Since the device's dimensions are already a significant fraction of the corresponding wavelength at 2 GHz, full wave simulation tools have been employed to more accurately assess the problem. The results reveal how the considered package concepts affect the overall parasitic device impedances and show a clear improvement of the parasitic impedance over each generation of package implementation. Furthermore, full wave analysis results are compared to method of moments results to emphasize the necessity of full wave simulations at these frequencies. Abstract : In this article, parasitic impedances of the source drain path of gallium nitride high electron mobility transistor packages are investigated and compared. The packages include already established versions, as well as future geometries and are simulated up until 2 GHz.